Exercise 1
Q1. Solve for
x
x
x
x
x
:
3
x
−
3
=
0
3
x
−
3
=
0
3x-3=0
3x - 3 = 0
3
x
−
3
=
0
Hint 1
Add
3
3
3
3
3
to both sides.
Now,
3
x
=
3
3
x
=
3
3x=3
3x=3
3
x
=
3
.
Hint 2
Divide both sides of the
=
=
=
=
=
by
3
3
3
3
3
.
Now,
3
x
3
=
3
3
3
x
3
=
3
3
(3x)/(3)=(3)/(3)
\frac{3x}{3}=\frac{3}{3}
3
x
3
=
3
3
.
Hint 3
Simplify
3
x
3
=
3
3
3
x
3
=
3
3
(3x)/(3)=(3)/(3)
\frac{3x}{3}=\frac{3}{3}
3
x
3
=
3
3
.
Q2. Solve for
y
y
y
y
y
:
2
y
3
=
2
2
y
3
=
2
(2y)/(3)=2
\frac{2y}{3} = 2
2
y
3
=
2
Hint 1
Multiply both sides by
3
3
3
3
3
.
Now,
2
y
=
6
2
y
=
6
2y=6
2y=6
2
y
=
6
.
Hint 2
Divide both sides by
2
2
2
2
2
.
Now,
2
y
2
=
6
2
2
y
2
=
6
2
(2y)/(2)=(6)/(2)
\frac{2y}{2}=\frac{6}{2}
2
y
2
=
6
2
.
Hint 3
Simplify
2
y
2
=
6
2
2
y
2
=
6
2
(2y)/(2)=(6)/(2)
\frac{2y}{2}=\frac{6}{2}
2
y
2
=
6
2
.